Analytic hierarchy process for multi-criteria site selection of utility-scale solar and wind projects - Rapal, Bryan Karl Anthony L. (Animo Repository, 2017)
The deployment of renewable energy technologies is also a socio-political decision, in as much as it is a technical decision. This can explain the success and failure of many renewable energy projects in the world. The present study proposes a new decision-making criterion for assessment of potential sites for utility-scale solar and wind project deployment, using the analytic hierarchy process (AHP) methodology. Considering data availability, the proposed metrics include potential social impact, local market characteristics, existing local infrastructure, disaster and climate risk, policies, and wind/solar intensity. Furthermore, various experts from academe, industry, policy making, and finance were interviewed to formulate the prioritization scores. The results from a case study in the Philippines show that local wind and solar intensity is still the top priority across all stakeholders, followed by the presence of renewable energy policies, and vulnerability to disaster and climate risks. The least priority is potential social impact. The results are presented via a geographical information system (GIS) map. Furthermore, existing renewable energy installations in the Philippines are assessed using the resulting criteria. The proposed method should be useful for the development of a national strategic deployment plan for emerging alternative energy technologies, and should be important for sustainable regional development. Copyright © 2017, AIDIC Servizi S.r.l. T